FACTORS DETERMINING THE CLINICAL SIGNIFICANCE OF DEPIPTIDYL PEPTIDASE 4 INHIBITORS IN THE TREATMENT OF PATIENTS WITH TYPE 2 DIABETES MELLITUS - Kurbonova Nozima Sobirjonovna (Scholar Express Journals, 2022)
The main components of the treatment of type 2 diabetes mellitus (DM) are hypoglycemic, lipid-lowering and antihypertensive therapy, while endocrinologists traditionally perceive the first of these components as the most important. Based on the results of several large prospective studies, it was concluded that compensation of type 2 diabetes close to normoglycemia is accompanied by an improvement in long-term prognosis in terms of the risk of macrovascular complications and death from cardiovascular diseases.
Keywords: Glycemic component; to normoglycemia; dyslipidemia